2021
DOI: 10.1002/eap.2326
|View full text |Cite
|
Sign up to set email alerts
|

Successful biological control of winter moth, Operophtera brumata, in the northeastern United States

Abstract: Winter moth, Operophtera brumata, native to Europe, invaded the northeastern United States in the late 1990s, where it caused widespread defoliation of forests and shade trees ranging from 2,266 to 36,360 ha/yr between 2003 and 2015 in Massachusetts. In 2005, we initiated a biological control effort based on the specialist tachinid parasitoid Cyzenis albicans, which had previously been introduced along with the generalist ichneumonid parasitoid Agrypon flaveolatum to control winter moth in Nova Scotia in the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Our curated moth parasitoid DNA barcode library integrating taxonomic, ecological, and molecular data therefore constitutes a reference point for monitoring changes in moth–parasitoid networks and their effects on moth population dynamics. As shown by the findings of Elkinton et al ( 2021 ), a deeper understanding of the factors driving moth population dynamics may eventually provide tools for reducing the frequency and severity of geometrid outbreaks also in the treeline forests of northern Europe.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our curated moth parasitoid DNA barcode library integrating taxonomic, ecological, and molecular data therefore constitutes a reference point for monitoring changes in moth–parasitoid networks and their effects on moth population dynamics. As shown by the findings of Elkinton et al ( 2021 ), a deeper understanding of the factors driving moth population dynamics may eventually provide tools for reducing the frequency and severity of geometrid outbreaks also in the treeline forests of northern Europe.…”
Section: Discussionmentioning
confidence: 95%
“…However, parallel changes in parasitoid communities, host–parasitoid associations, and parasite‐mediated indirect interactions among moth species are expected, but are difficult to document (Kankaanpää et al, 2020 ; Vindstad et al, 2013 ). A substantial “reservoir” of additional geometrid moth parasitoids is known to exist further south in Europe, where moth population eruptions are less dramatic (Elkinton et al, 2021 ; Früh, 2014 ; Kenis et al, 2005 ; Noyes, 2022 ; Tikkanen et al, 1998 ; Vindstad et al, 2013 ; Wylie, 1960 ). Our curated moth parasitoid DNA barcode library integrating taxonomic, ecological, and molecular data therefore constitutes a reference point for monitoring changes in moth–parasitoid networks and their effects on moth population dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The biological control of winter moth in North America is one of the best-known examples of the successful use of importation biological control (Van Driesche et al, 2010) to reduce the ecological and economic impacts of a non-native forest defoliator with a broad host range (Elkinton et al, 2015;Embree, 1966;Kimberling et al, 1986;Roland & Embree, 1995). Recently, Elkinton et al (2021) showed that the introduction of a single specialist natural enemy to the Northeast was able to convert winter moth to non-pest status. These introduced natural enemies have been incredibly effective at reducing the abundance of winter moth in high density locations, but at low densities, numerous authors have found that native pupal parasitoids play an important role in regulating winter moth population sizes (Frank, 1967a(Frank, , 1967bHorgan, 2005;Horgan & Myers, 2004;Latto & Hassell, 1987;Raymond et al, 2002;Roland, 1994;Roland & Embree, 1995, Broadley 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, populations were identified in Oregon as a pest in hazelnut (filbert) orchards in the 1950s (Kimberling, Miller, & Penrose, 1986), British Columbia as a pest in apple orchards and of urban trees in the 1970s (Gillespie, Wratten, Cruickshank, Wiseman, & Gibbs, 1978), and most recently in the northeastern United States (hereafter, the "Northeast") as a pest of blueberries, cranberries, and many native deciduous trees in the 1990's (Elkinton et al, 2010;Elkinton, Liebhold, Boettner, & Sremac, 2014). Each of these regions were likely the result of independent invasions from Europe , and while successful biological control programs have reduced the abundance and economic impacts of this important pest in each invaded region (Elkinton, Boettner, Liebhold, & Gwiazdowski, 2015;Elkinton, Boettner, & Broadley, 2021;Kimberling et al, 1986;Roland & Embree, 1995), populations of winter moth continue to persist at low densities in each location. Previous work in this system has shown that winter moth and Bruce spanworm hybridize readily in the field (Andersen et al, 2019;Elkinton et al, 2010Elkinton et al, , 2014Havill et al, 2017).…”
mentioning
confidence: 99%
“…Through cooperative interagency efforts including the TWPP in the US, spread and damage have been greatly reduced in some cases by setting goals to prioritize problematic invasive (56,97,120,195). They are also sustainable in that they undergo natural genetic feedback, often with faster generation times than the pest, thereby preventing loss of efficacy due to pest evolution (103,105,120).…”
Section: Pest Managementmentioning
confidence: 99%